2014
DOI: 10.1002/ijch.201300121
|View full text |Cite
|
Sign up to set email alerts
|

Molecular‐Level StructureProperty Relationships in Biogenic Calcium Carbonates: The Unique Insights of Solid‐State NMR Spectroscopy

Abstract: The biomineralization process produces materials with exceptional microscopic, morphologic, and mechanical qualities, which are finely tuned for specific functionality. This control of the properties is obtained through interactions with bioorganic and inorganic molecules that regulate the formation and/or become incorporated into the final biomineral. Although the interfacial regions comprise a minute fraction of the mineral, they are of paramount importance. Modern solid-state NMR spectroscopy techniques ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 90 publications
1
14
0
Order By: Relevance
“…We applied solid-state NMR spectroscopy for identifying the bioorganic molecules that are bound to the mineral particles and, therefore, possibly responsible for the nucleation of the mineral phase. To examine these structures, we used a combination of the 1 H-13 C cross-polarization (CP) and single-pulse 13 C NMR techniques (19). The former consists of a CP magnetization transfer from 1 H nuclei to nearby 13 C nuclei and enables the detection of carbon species localized in hydrogen-rich chemical environmentsnamely, the SOM and the interfacial carbonates (i.e., those exposed to the mineral/organic interface).…”
Section: Detection Of Highly Disordered Environments In Coral Skeletonmentioning
confidence: 99%
See 1 more Smart Citation
“…We applied solid-state NMR spectroscopy for identifying the bioorganic molecules that are bound to the mineral particles and, therefore, possibly responsible for the nucleation of the mineral phase. To examine these structures, we used a combination of the 1 H-13 C cross-polarization (CP) and single-pulse 13 C NMR techniques (19). The former consists of a CP magnetization transfer from 1 H nuclei to nearby 13 C nuclei and enables the detection of carbon species localized in hydrogen-rich chemical environmentsnamely, the SOM and the interfacial carbonates (i.e., those exposed to the mineral/organic interface).…”
Section: Detection Of Highly Disordered Environments In Coral Skeletonmentioning
confidence: 99%
“…S3). The spectra from the bulk of the carbonates display a single resonance; this resonance is symmetric and centered at d 13 C = 171.0 parts per million (ppm), which is characteristic of crystalline aragonitic environments (19). In contrast, the spectra from the interfacial carbonates display a much broader resonance that is asymmetric and whose maximum intensity is slightly lower (d 13 The three CRM maps for each section were generated on the basis of the relative intensity distribution of (i) two characteristic Raman bands of aragonite-namely, the translational lattice mode at 152 cm −1 (A1 and B1) and the v 1 symmetric stretching mode of the CO 3 2units at implies that the interfacial carbonates form highly disordered, amorphous environments a few nanometers thick (20) that coat the aragonite crystals.…”
Section: Detection Of Highly Disordered Environments In Coral Skeletonmentioning
confidence: 99%
“…However, they found no evidence of large scale separation of Ca 2+ and CO 3 2-as suggested by Goodwin et al 16 . The local environment of water has also been extensively studied with NMR on both biogenic 13,[19][20] and synthetic ACC 11,[21][22][23][24][25] . These studies reported both translationally restricted and mobile water as well as hydroxide ions in ACC 11,23,25 .…”
mentioning
confidence: 99%
“…On the latter a single thin resonance at ( 13 C) = 171.5 ppm is observed that corresponds to carbonate from crystalline aragonite. 11 The resonances of the organic matrix and of -chitin in particular are not observed due to their very low proportion in the sample (less than 5 w%). Exposed carbonates, observed in the CPMAS spectrum at long contact time, exhibit a slightly shifted resonance at higher field (170.5 ppm) and of larger linewidth due to higher local disorder as compared to carbonates in crystalline environment.…”
Section: Bone Apatite Organo-mineral Interfacementioning
confidence: 99%
“…Solid-state NMR is in principle the method of choice to access a fine description of biomineralized tissues. 9,10,11 The intrinsic low sensitivity of this spectroscopy limits however its applicability to the investigation of surfaces and interfaces in materials of low specific surface area where the selective observation of surface versus bulk species is extremely challenging. In that context, Dynamic Nuclear Polarization (DNP) has recently emerged as an appealing technique to drastically enhance the sensitivity of solid-state NMR spectroscopy and, in particular, to amplify signals at surfaces in an approach called DNP SENS (DNP Surface Enhanced NMR Spectroscopy).…”
Section: Introductionmentioning
confidence: 99%